Book Review: R. McMahon (ed.), National races. Transnational Power Struggles in the Sciences and Politics of Human Diversity, 1840-1945 - Francesca Zantedeschi (Studies on National Movements, 2022)
Book review of R. McMahon (ed.), National races. Transnational Power Struggles in the Sciences and Politics of Human Diversity, 1840-1945